(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Travel and Tours Management System is an integrated and innovative solution designed to handle travel and tour transactions for tour operators, travel agencies, and customers. This comprehensive system provides end-to-end solutions, from hiring new employees and logistics for equipment to financial expenses and administration. One of the key features of Core Transaction I management is the creation of unique tour packages, including itineraries, amenities, local hotels and staycations, rental vehicles, and booking pages for clients. The system ensures high-quality services and experiences for clients with reliable service providers. The Travel and Tour Core Transaction I System from the Mblitz Company provides an up-to- date and modern approach to tour creation, management, and booking. The system offers a comprehensive tour management solution for tour operators and travel agencies, including creating and configuring tours, managing customer tour itineraries, booking transportation and hotels, and processing tour bookings. New features: web-based & responsive system, tour/itinerary development, hotel/transportation listing, and Gcash payment. Mblitz Travel & Tours improves its manageability and customer accessibility with these enhancements. The Mblitz Company’s Travel and Tour Core Transaction I System is a modern and complete platform that offers a streamlined approach to tour creation, management, and booking. Its web-based, flexible interface enables simple tour customization and control of customer itineraries, transportation, and hotel bookings. Customers can easily browse, book, and pay using Gcash, reducing workload for operators and agencies and increasing client retention. The backend efficiently handles reservations and bookings, while the user-friendly interface optimizes operations and improves customer experiences.